The Art of Empathy: Employing the Arts in Social Inquiry with Poor, Working-Class Women - Foster, Hamar (Social justice, 2007)
Part of a special issue on the relationship between art, identity, and social justice. A study was conducted to explore the use of the arts in conducting research among poor, working-class women. Data were obtained from field work, art projects, and interviews conducted as part of the Sure Start program involving working-class women from a deprived area of Great Britain. Findings revealed that those who participated in the project cultivated relationships, made important discoveries about themselves, and gained a rare opportunity to share the reality of their lives with an audience that included policymakers and professionals. Findings also revealed that artistic, emotional expression facilitated an accurate evaluation of the success of the program. Findings indicated that the arts and humanities have much to teach social sciences in the area of capturing life as it is and communicating it to a wider audience. Findings are discussed in detail.